Printed electronics for smart water technology sensor - Koh, Joy Yuan En (Nanyang Technological University, 2021)
In recent years, the appeal of membrane technology has surged in process water production, wastewater treatment and drinking water. There are challenges posed such as fouling problems and consequently membrane replacement resulting in higher operating cost. Due to irreversible membrane fouling, attention has been drawn over the years towards electrochemical techniques to circumvent irreversible fouling. Hence, this project focuses on the fabrication of sensing electrodes for electrochemical testing to accurately detect membrane fouling. During the process, electrodes and coupons with gold nanoink were printed and printing parameters were varied using an aerosol jet printer. The electrodes and coupons are then subjected to various tests such as field emission scanning electron microscope, resistance, adhesion, surface treatment and electrical testing. The objective of this project is to identify the best combination of condition and methodology that can be used to fabricate electrode for electrochemical testing to assist with the early detection of membrane fouling.